(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
This contribution looks at the interactions between cultural rights and investment law and investigates the protection afforded to African cultural considerations in international investment law. If it is generally accepted that culture plays a central role in the continent’s quest for development and is an identifying factor for African peoples, how does international investment law protect African cultural considerations, knowing that the protection granted to investments may have an impact on certain cultural aspects of the countries in which they are being executed? Although cultural considerations have gradually made their way into the normative landscape of investment law, this article argues that taking these considerations into account remains, in many respects, insufficient in investment litigation. The article goes further to discuss certain reforms to better protect cultural considerations and thus allow the cultural lever to fully play its role in achieving the Africa we want.